Peran Kegiatan Edukatif dalam Membangun Mindset Positif di Kalangan Masyarakat terhadap Investasi Perdagangan Komoditi Berjangka - Putri, Kanaya Amelia; Zawawi, Zawawi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The rise in fraud cases is one factor contributing to the decline in public trust in investments in the commodity futures trading sector. The abundance of illegal investment platforms often creates a negative perception among the public that investing is a detrimental activity. Therefore, it is crucial to increase public literacy and understanding regarding the legal aspects of commodity futures trading. This activity aims to provide public understanding and education regarding the legality and clear regulations of investment through a digital-based outreach approach. Through this outreach, it is hoped that the public will develop a more open mindset and understand the risks of investing.